2020
DOI: 10.1007/s12310-020-09390-x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Severity and Responses to Reportable Student Self-Harm and Suicidal Behaviours in Schools: A One-Year Population-Based Study

Abstract: School staff have a unique opportunity to detect and respond to mental health issues including self-harm and suicidal behaviour in adolescents. There is limited knowledge about how these incidents are managed in schools. This study aims to understand the incidence rates, perceived severity and management of self-harm and suicidal behaviour incidents by schools. A total of 1525 school incidents were analysed for rate, severity and response. Pearson's χ 2 test was used to understand incident rates of self-harm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Schools are well placed to identify and intervene with students who self‐harm and often school staff are first to notice or hear about concerning behaviours (Berger, Hasking, & Reupert, 2014a). Results of a recent Australian study showed that self‐harm and suicidal behaviour incidents account for 5.05% of all incidents reported by schools to emergency services are 1.43 time more likely to have police involvement and 8.37 times more likely to require an ambulance, compared to other incidents that caused harm to students (Crowe, Townsend, Miller, & Grenyer, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Schools are well placed to identify and intervene with students who self‐harm and often school staff are first to notice or hear about concerning behaviours (Berger, Hasking, & Reupert, 2014a). Results of a recent Australian study showed that self‐harm and suicidal behaviour incidents account for 5.05% of all incidents reported by schools to emergency services are 1.43 time more likely to have police involvement and 8.37 times more likely to require an ambulance, compared to other incidents that caused harm to students (Crowe, Townsend, Miller, & Grenyer, 2020).…”
Section: Introductionmentioning
confidence: 99%